S20 Suicidal ideation, depression and anxiety in chronic cough. (11th November 2022) - Hirons, B; Rhatigan, K; Simpson, A; Kesavan, H; Turner, R; Hull, J; Docherty, M; Jolley, C; Birring, SS; Cho, PSP
Abstract : Introduction: Chronic cough is associated with significant psychosocial co-morbidities. We investigated the prevalence of suicidal ideation, depression and anxiety and their relationship with cough severity. Methods: Consecutive patients with chronic cough at a specialist clinic prospectively completed Patient Health Questionnaire (PHQ9) for depression and suicidal ideation, Generalised Anxiety Disorder Assessment (GAD7), cough severity and intensity visual analogue scales (VAS), Leicester Cough Questionnaire (LCQ), Patient Global Impression of Severity (PGIS) of cough, and objective cough frequency (CF) assessed with Leicester Cough Monitor. Suicidal ideation was defined as score >0 on item 9 of PHQ9. Case notes were reviewed for clinical characteristics. Results: 339 participants completed the assessments; 104 (31%) and 69 (21%) reported symptoms of at least moderate severity of depression and anxiety (PHQ9 and GAD7 > 10) respectively. Suicidal ideation was reported in 36 (11%) and was associated with younger age, worse cough severity and intensity VAS, LCQ, PGIS, total PHQ9 and total GAD7 scores ( table 1 ). Depression and anxiety symptoms were associated with cough severity VAS (r=0.41; r=0.31) and LCQ (r=-0.58; r=-0.46) all p<0.0001 respectively, but not with sex, diagnosis, cough duration or objective CF (all p>0.16). Female patients had worse LCQ, VAS and PGIS scores, and higher CF than males (all p<0.017). There was no difference in total PHQ9, GAD7 or suicidal ideation (all p>0.44) between the sexes. Conclusion: Suicidal ideation and symptoms of depression and anxiety are common in chronic cough, and are associated with cough severity and cough-specific health status. Further studies should investigate the direction of the relationship between psychological morbidity and chronic cough, and effective therapies.